Phytochemical Screening and Effectiveness of Calotropis procera Ait. R. Br. (Asclepiadaceae) Leaf Powder Against Cowpea Bruchid (Callosobruchus maculatus Fab.) (Coleoptera: Chrysomelidea) - , Raoul Borkeum Barry; , Michel Awoumé Ebéné; , Tagne Gabriel Fotso; , Christian Ndouyang; , Bruno Olivier Rouama Paggo; , Albert Ngakou; , Nchiwan Elias Nukenine (Archives of Current Research International, 2025)
Cowpea grain is a legume that plays an important role in the diets of many populations. However its production is limited by several biotic and abiotic constraints, including the attack of Callosobruchus maculatus beetles. In this way, Calotropis procera leaf powder extract was evaluated in the ambient laboratory conditions (t ≈ 25.74 ± 1.03°C; r.h. ≈ 71.48 ± 2.04%) for adult mortality, F1 progeny reduction and seed damage, as well as on seed viability. Leaf powder was tested at 2, 4, 8 and 16 g/kg with four replications. Seed viability was assessed using seeds preserved for two months at a single concentration of 16 g/kg. Results showed that significant mortalities of C. maculatus on treated cowpea grains was recorded with leaf powder at all the concentrations, and they increased with the increasing of concentrations used and exposure periods. At the lowest concentration of 2 g/kg, C. procera leaf powder recorded more than 85% of mortality 1 day after exposure. The highest concentration (16 g/kg) caused almost complete adult mortality. The leaf extract used in this study showed complete inhibition in the F1 progeny emergence of C. maculatus within in the concentration of 8 g/kg, and considerably reduced grain damage caused by C. maculatus. Seeds viability were not affected by C. procera leaf extract used. Considering these results, C. procera leaf powder extract could be a good alternative insecticide for cowpea grains protection during storage.